Ruptured Pseudoaneurysm of Branch of Profunda Femoral Artery during Revision Total Hip Arthroplasty: a Case Report: Case report for rupture pseudoaneurysm of branch of Profunda Femoral Artery during Revision Total Hip Arthroplasty - Wattanapreechanon, Pichayut; Hongku, Natthapong (Vajira Medical Journal : Journal of Urban Medicine, 2023)
A ruptured pseudoaneurysm is a rare but potentially fatal complication during revision total hip arthroplasty. We report a case of a 46-year-old female with a rupture of a pseudoaneurysm at the branch of the left profunda femoral artery during revision total hip arthroplasty. The patient presented with dislocation of the left total hip arthroplasty, which failed closed reduction. During the revision surgery, a massive pulsatile bleeding occurred, which required an emergent vascular surgeon consultation to repair the ruptured pseudoaneurysm. It was later confirmed to be located at the branch of the left profunda femoral artery. Although rare, we recommend performing pre-operative CT angiography and consulting with a vascular surgeon before attempting revision total hip arthroplasty in patients with atypical symptoms, such as unusual thigh swelling and unexplained anemia.